A Review Of Islamic Criminal Law On The Crime Of Military Desertion - Anjani, Meisarah Tri; Iwan, Iwan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Desertion is one of the most common military cases tried in Indonesian military courts. So that this has a negative impact, both on the military unit, society, and the state. The increase in desertion cases raises a perspective that the positive law governing criminal sanctions for desertion does not have a deterrent effect or preventive effect on military personnel. Therefore, the purpose of this research is to examine military desertion in the perspective of Islamic criminal law with a focus on the form of desertion crime, its causative factors, and criminal sanctions. This research uses a normative research method (legal research) with a comparative approach. The results of this study indicate that desertion in positive law is a pure criminal offense things only military personnel have the ability of committing. Whereas in Islamic criminal law, desertion can apply to all believers, unless there is an excuse that makes it not obliged to jihad. The criminal sanction for desertion in positive law is in the form of imprisonment and can also be coupled with punishment in the form of dismissal from military service. While in Islamic criminal law, the criminal sanction is in the form of ta'zir punishment in the form of social sanctions, such as perpetrators who run away from the battlefield are prohibited from talking to all Muslims for fifty days. Based on several opinions of fiqh scholars, ta'zir punishment aims to dissuade the offender and prevent the occurrence of a prohibited act.